Dari Layar ke Gerak: Narasi Orang Tua tentang Mengajak Anak Berpartisipasi dalam Aktivitas Fisik untuk Membatasi Paparan Layar - Amelda, Dea; Wijaya Kuswanto, Cahniyo (UNIB Press, 2025)
In the digital age, increased screen time among children has become a major concern affecting their overall development. Excessive screen exposure negatively impacts physical activity levels, reduces social interactions with the environment, and poses various health and psychological risks. This study explores parental strategies for redirecting children's attention from screens to physical activities. Using a qualitative approach, data were collected from 10 parent-child pairs (children aged 4-6 years) through interviews, observational studies, and documentation. The findings identified several effective parental strategies: direct engagement through shared play activities, creating supportive home environments with appropriate facilities, and facilitating peer social interactions that successfully reduce children's dependence on digital devices. While online gaming presents significant challenges, the results demonstrate that children's interest in physical activities can be maintained over screen-based entertainment through consistent parental intervention. This research provides valuable insights into parental strategies focusing on direct interaction and home-based play environments to minimize screen exposure in early childhood.